(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper aims to explore the significance and role of weekly market centers in rural development, focusing on the Jonai sub-division of Dhemaji district, Assam. Weekly market centers, commonly known as "haats," play a vital role in the socio-economic fabric of rural communities. The study investigates the functioning, impact, and challenges faced by these market centers and their contribution to the overall development of the region. The research employs a mixed-methods approach, including surveys, interviews, and case studies, to gather primary data from market participants, local authorities, and community members. The findings provide valuable insights into the socio-economic dynamics of the weekly market centers and their potential for fostering rural development in Jonai sub-division.